(untitled) (Journal of Asian Development Studies, 2025)
The aim of this study was to develop students’ critical thinking skills by applying questioning techniques as a tool. The study employing action research approach adopted the spiral model of action research characterized by iterative steps of reconnaissance, planning, action, observation/reflection and re-planning. This cyclical process was repeated in a spiral fashion. The findings suggest that questioning is one of the effective pedagogical techniques to foster students critical thinking skills. The findings reveal four phases of critical thinking skills development. In the initial phase / level of intervention, most of the students almost reproduced the memorized / recalled responses instead of demonstrating critical thinking skills. In the second phase, most of the students somewhat departed from recalling level and demonstrated the ability to analyses the issue from multiple perspectives. In the third phase, most of the students developed the ability to understand the complex interconnections of issues followed by the fifth phase in which students developed action-oriented critical thinking skills to some extent. The study makes strong recommendations for teachers to employ questioning techniques as a tool for developing students’ critical thinking skills.